Gaya dan Strategi Belajar Bahasa Arab Mahasiswa Alumni Madrasah dan Non Madrasah - St Kuraedah (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2022)
This study aims to investigate Arabic learning styles and strategies for madrasah (MA) and non-MA (non MA) alumni students. This mixed method with concurrent triangulation model (a mixture of quantitative and qualitative in a balanced way) used questionnaires combined with interviews, observations and documentation. The findings showed that MA and non MA alumni did not show significant differences in learning styles. They use audio, visual and kinesthetic learning styles together. Likewise, the tendency to become an activist, theorist, pragmatic and reflector learner is almost evenly distributed based on their learning needs. The Arabic learning strategies of MA and non MA alumni students in some circumstances show similarities, they jointly use cognitive, metacognitive, and social strategies (Oxford & Burry-Stock, 1995). To solve the learning problems they face, non-MA alumni use more social strategies by finding study friends and joining online study groups.Keywords: Arabic language; learning strategy; learning style; madrasah alumni; nonmadrasah alumni